Child-rearing Anxiety of Mothers with Infants Hospitalized in NICU. (December 2016) - Suzuki, M.; Hasui, S.; Ishimura, M.; Arioka, A.; Tanimoto, K.
Abstract : Background: In Japan, the mothers who have the anxiety of child rearing is increasing because of declining birth rates and increase in nuclear families. It is recognized as that the anxiety of child rearing in mothers who have their infants hospitalized in the Neonatal Intensive Care Unit is high. Objective: To examine child rearing anxiety, psychological and physical distress, and social support for mothers with infants hospitalized in theNeonatal Intensive Care Unit. Methods: A questionnaire including the Childcare Stress Scale (with subscales for childcare anxiety and social support) and the General Health Questionnaire was conducted with 100 mothers. Participants were divided into three groups: mothers whose infants were hospitalized (hospitalized group); whose infants were discharged one month earlier (one-month discharge group); and whose infants were discharged one year earlier (one-year discharge group). Results: There was a correlation between General Health Questionnaire and child caring anxiety and between General Health Questionnaire and social support for the hospitalized group. In the one-month discharge group, there was a correlation between General Health Questionnaire and child caring anxiety. In the one-year discharge group, there was a correlation between General Health Questionnaire and child caring anxiety, General Health Questionnaire and social support, and child caring anxiety and social support. For the one-month discharge group, a significantly high score was seen in time of child caring for mothers who work. Also, a high score was seen in bad feelings towards their children and total score of child caring anxiety for mothers who could not return to their hometowns. For the one-year discharge group, the score for child caring anxiety was high for mothers who hadn't returned to their hometowns. For mothers with other children, the scores for bad feelings towards their children and General Health Questionnaire were high. Conclusion: This study suggests the importance of paying attention to the psychological and physical condition of mothers whose infants are hospitalized, and in supporting their social environment.